The Relationship Between Corporate Social Responsibility and Tax Avoidance: Evidence From Chinese Listed Companies - Huang, Xiting (2019)
Currently, corporate social responsibility (CSR) and tax avoidance has captured academic’ interest. Meanwhile, some researchers have started to investigate the relationship between CSR and tax avoidance. In addition, an increasing number of Chinese companies have participated in CSR activities, as well as the Chinese government and other organisation have also made great efforts to promote the development of CSR. Under such circumstance, growing interest has been drawn to quantity and quality of CSR reports. Therefore, this dissertation, based on a sample of Chinese listed companies from 2014 to 2018, further explored the relationship between CSR and corporate tax avoidance. The data of CSR and other financial indicators was collected from Rankins CSR Ratings (RKS) database and China Stock Market and Accounting Research (CSMAR) database respectively. According to the empirical results of fix effect model, it was found that there was a negative correlation between corporate social responsibility and corporate tax avoidance. The results indicated that the higher the participation of CSR activities of a company was, the lower probability of tax avoidance was. Moreover, the empirical results of this dissertation also proved that CSR had a positive impact on increased corporate tax awareness, suggesting that Chinese companies should integrate CSR into their corporate culture.